Morphological changes in the skin after administration ofsilver nanoparticles. - Syrma, O. I.; Skobeeva, V. M.; Ulianov, V. O. (Морфологія / Morphologia / Morfologìâ, 2014)
Background. Silver nanoparticles are of interest to be used as antimicrobial agents in wound dressings and coatings in medical devices, but potential adverse effects have been reported in the literature. The most pronounced effect of silver nanoparticles and the role of particle size in determining these effects, especially in comparison to silver ions, are largely unknown. Objective. To investigate the morphological and functional changes in the skin tissues during intradermal injection of silver nanoparticles. Methods. Spherical silver nanoparticles of 30 nm were used. The experiment was performed on 140 Wistar rats. The effect after subcutaneous injection of 0.01 ml of silver nanoparticles solution was examined on the 1st, 3rd, 7th, 14th, 21st, 30th, 45thday.Standard histological techniques were used. Results. It was shown that after the injection of silver nanoparticles there is a complex of reactive changesin the skin, which is realized in severalphases. Immediately after injection the phase of inflammation begins. Later it is replaced with the phase of regenerative histogenesis with the formation of granulation tissue and further is finished in the phase of adaptive remodeling. Conclusion. Morphological and functional changes after the intradermal injection of silver nanoparticles are based on the pattern of normal histogenesis that occurs at the site of injection and do not affect the intact zone.